Can diesel internal injector deposits form via an electrokinetic mechanism?. (15th April 2023) - Slavchov, Radomir I.; Radev, Ivan; Philippi, Wladimir; Peinecke, Volker; Clarke, Stuart M.; Filip, Sorin
Highlights: Electrokinetic mechanism for formation of deposits in diesel injectors is proposed. Streaming current upon injection is compensated by earthing current inside injectors. Earthing current produces reactive species at the metal|fuel interface. Two types of degradation products form: electrolytes and gum. Experiment shows that direct oxidation dominates degradation in fully formulated fuel. Abstract: A hypothetical electrokinetic mechanism of wear and deposition inside fuel injectors has been analysed theoretically and experimentally. It involves conjugated electrokinetic and earthing electric currents. The flow of fuel through the orifice of the injector produces a streaming current proportional to the ς-potential of the metal| fuel interface. The streaming current leads to an accumulation of streaming potential between the fuel in the combustion chamber and the fuel in the internal injector chambers. This potential drives an earthing current, which, at steady state, compensates the streaming current. The earthing requires electrochemical reactions to transfer charge through the metal| fuel interface of the internal parts of the injector. The hypothesis investigated here is that the reactions produce ion-radicals, which (i) initiate radical chains leading to oxidized deposit formation; (ii) produce fuel-insoluble electrolytic products. The hypothesis is tested experimentally using a rig where current is passed through two steel electrodes in fully formulated diesel at constant voltage. Accumulation of oxidation products (gum) in the diesel is observed with and without current, up to phase separation. The rate of deposition in the rig is found to be dominated by direct oxidative degradation rather than the electrokinetic mechanism.